Self-Reference enhances memory for multi-element events judged likely to happen in young and older adults. Issue 10 (26th November 2019) - Hou, Mingzhu; Grilli, Matthew D.; Glisky, Elizabeth L.
ABSTRACT: We investigated whether the strategy of self-reference can benefit memory for multi-element events, a kind of relational memory that is relatively less studied but highly relevant to daily life. Young and older adults imagined different person-object-location events with reference to themselves and two famous others (i.e., George Clooney and Oprah Winfrey), rated the likelihood that each event would happen, and then completed incidental memory tests on different pairs of elements within the event. We found that self-reference enhanced memory for object-location and person-object pairs in both age groups. Such self-reference effects were observed consistently only for events rated as likely to happen. There was also an overall memory advantage for the higher-likelihood events, which did not differ between young and older adults. Further, the self-reference effects were not correlated with memory functioning in either age group. Retrieval of within-event associations showed a significant level of dependency, which did not differ as a function of reference condition or likelihood category. These findings highlight the ways in which self-reference and prior knowledge improve relational memory, and suggest that the advantage of self-reference is not attributable to increased dependence of elements within complex events.